Collective Bargaining in the Maritime Fishing Industry: Recent Developments - Gurdon, Michael; Wright, David (Relations industrielles / Industrial Relations, 1984)
This paper summarizes recent changes in the Canadian fishing industry, with particular emphasis on the Maritime region, traces the rise of a new union seeking to represent inshore fishermen, and describes the resulting collective bargaining legislation in New Brunswick.